2009
DOI: 10.3111/13696990903093537
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence, healthcare utilisation and costs in adult patients with major depressive disorder: a comparison between escitalopram and other SSRI/SNRIs

Abstract: Escitalopram may be associated with lower healthcare utilisation and costs among adult MDD patients compared to other SSRI/SNRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
3
19
0
3
Order By: Relevance
“…Escitalopram, an enantiomer of citalopram, is another SSRI antidepressant (Wu et al 2009;Pan et al 2011). In our model, we observed that escitalopram reduces the levels of proinflammatory cytokines (see above) and attenuates depressive-like behavior in MI rats without modifying their sleep (Bah et al, 2011).…”
Section: Escitaloprammentioning
confidence: 99%
“…Escitalopram, an enantiomer of citalopram, is another SSRI antidepressant (Wu et al 2009;Pan et al 2011). In our model, we observed that escitalopram reduces the levels of proinflammatory cytokines (see above) and attenuates depressive-like behavior in MI rats without modifying their sleep (Bah et al, 2011).…”
Section: Escitaloprammentioning
confidence: 99%
“…Клиническая эффективность антидепрессантов в повседневной практике изучена в целом недоста-точно [44][45][46]. В широком понимании клиническая эффективность включает и безопасность (перено-симость) лечения.…”
unclassified
“…В широком понимании клиническая эффективность включает и безопасность (перено-симость) лечения. Так, 2,5-летний анализ популя-ционной выборки из 10 465 пациентов показал [46], что получавшие эсциталопрам реже меняли антиде-прессант по сравнению с лечившимися циталопра-мом и реже повторно госпитализировались. В одном из метаанализов [47] оценивалась эффективность разных антидепрессантов и было выделено три ан-тидепрессанта -эсциталопрам, нортриптилин и дулоксетин по критерию возможности достижения ремиссии в течение 8-12-недельного лечения гиб-кими дозами.…”
unclassified
See 1 more Smart Citation
“…6 Apart from the impact on the quality of life, the potential result of suboptimal treatment of depression is increased direct costs to the health system because of more outpatient encounters and the addition of inpatient care if symptoms become severe. 9 The purpose of this paper is to develop a conceptual model to explore the relationship between the presence of depressive symptoms and secondary physical complications.…”
Section: Introductionmentioning
confidence: 99%